Calculating Intrinsic and Extrinsic Camera Parameters Based on the PnP Problem - Yue Zhao; Yalin Wang; Qian Cui (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
The classical PnP problem is premised on given intrinsic camera parameters. However, for unknown intrinsic camera parameters, given n space points in a world coordinate system and their coordinates in an image coordinate system, the extrinsic camera parameters can be determined. Regarding the existence and uniqueness of a solution for the classical PnP problem, for 4 control points in a plane and an uncalibrated camera, a set of linear equations can be solved based on the correspondence between the space points and the image points. The results show that this approach is feasible and has high calculation precision.